Pengaruh Tingkat Margin Terhadap Keputusan Pembiayaan Pada Produk Syariah Dengan Religiusitas Sebagai Variabel Moderasi - Riza Warnain; Heru Aulia Azman (Universitas Dharma Andalas, 2023)
This study aims to understand the influence of the margin level on the decision of customers to choose Grya products with religiousity as a variable of moderation. The study was conducted at PT. Bank of Indonesia KC Bukittinggi Sudirman 2. The research population is the entire customer who took Grya financing on PT. Bank of Indonesia KC Bukittinggi Sudirman 2. Sampling used the Slovin technique with a total of 100 respondents. Data analysis with moderated regression analysis (MRA). The results showed that the interaction between the margin level variable (X) and the initial customer outcome (Y) coefficient of the Margin Level had a positive value of 0.660 and the significance value was 0.429 > 0.05 and the religiousness (Z) moderated the customer outcomes (Y), with the negative cofficient value of -0.007 signifying value of 0,843 was 0.843 > 0.05. This indicates that religiousity is unable to moderate the influence of the margin level on the customer’s decision to choose a grya financing product. The results of the study showed that religiousness was able to weaken the influence between the margin level and customer decision but was not significant, this was demonstrated by the regression result with a negative coefficient of -1,487 and a decrease in the determination factor result after the MRA test from 54% to 53.5%. Thus, it is concluded that